The Role of Interleukin 10 Genetic Variations in Pulmonary Tuberculosis: Perspectives of Genetics, Pathogenesis and Immunology - Anggraini, Debie (Universitas Baiturrahmah, 2024)
Pulmonary tuberculosis remains a significant global public health challenge. In efforts to overcome this disease, a deeper understanding of the role of individual genetics, such as IL-10 genetic variation, in the response to M. tuberculosis infection is critical. Research that has been conducted shows that IL-10, which has an important role in regulating the immune response, can also influence the development of TB. Genetic variations in the IL-10 gene play a role in determining the extent of the immune response to TB infection and an individual's risk of this disease. The interaction between Treg cells, IL-10, and TB is also an important aspect in the pathogenesis and management of TB. Although Treg cells and IL-10 have a role in controlling excessive inflammation, too much of either can dampen the immune response needed to overcome infections. The implication of this research is that the development of more targeted and personalized therapy is an important step in overcoming TB. The use of individual genetic knowledge, such as IL-10 genetic variations, can help design more effective therapies and improve patient prognosis. However, challenges such as drug resistance and the complexity of genetic-immunological interactions remain challenges that need to be overcome in TB management. Overall, this study shows the importance of involving the fields of genetics and immunology in global efforts to address pulmonary tuberculosis. With a deeper understanding of the factors that influence the immune response to TB infection, we can hope to develop more effective strategies in the prevention, diagnosis and treatment of this disease and reduce the burden of TB worldwide.